Paleoenvironmental conditions of the late Miocene "Entrerriense" epicontinental sea: A case study of the Camacho Formation, SW Uruguay. (October 2021) - Aumond, Gustavo N.; Kochhann, Karlos G.D.; Netto, Renata G.; de Souza, Laís V.; Sedorko, Daniel; Horodyski, Rodrigo S.; Almeida Júnior, Flavio N.; Verde, Mariano
Abstract: Marine sediments deposited during late Miocene transgressive events are recorded over large onshore areas in southeastern South America, characterizing the "Entrerriense Sea". In Uruguay, these deposits crop out at the coast of the Department of Colonia, and are assigned to the Camacho Formation, which is well-known by its abundant fossil content. Nevertheless, high-resolution geochemical proxy records within the Camacho Formation succession are not yet available. Our goals are: (1) to assess in high-resolution the paleoenvironmental changes recorded by the marine and/or marine-influenced strata of the Camacho Formation in Uruguay; (2) to explore possible links between local responses and global climate shifts that occurred during the late Miocene. To achieve these goals, we applied a multi-proxy approach, in which sedimentary facies and trace fossil occurrences were compared with geochemical and physical properties records measured in high-resolution within the exposed succession of the Camacho Formation. Our results suggest that these strata record a shallowing-upward trend, also characterized by deposition in gradually more proximal settings [increasing-upward trends in log(Zr/Rb) and log(Ti/Rb)], coupled to increased influence of freshwater input in the upper half of the studied sedimentary succession (decreasing-upward Sr/Ba trend). Considering previously published ages for the Camacho Formation, we infer that this shallowing-upward trend was related to the high latitude cooling and/or ice volume expansion occurred between 7.2 and 6.9 Ma, and the associated long-term sea level fall from 7.2 to 6.5 Ma. These trends occurred in tandem with the onset of more humid climate conditions (recorded by the uppermost strata of the studied succession), which were likely related to the latitudinal migration of climatic belts. Highlights: The Camacho Formation records a shallowing-upward trend in a shallow marine setting. More proximal settings were likely related to sea level fall at 7.2–6.5 Ma. Paleoclimate became progressively wetter within the studied succession. Uppermost strata of the studied succession record increased freshwater influence.